Análise de estratégias de gestão zootécnica em sistemas de produção de bovinos leiteiros. - Ramos, Carlos Eduardo Crispim de Oliveira (2008)
With the aim to propose a functional methodological approach in dairy production's systems, it was done a field research in 19 milk farms according objective criteria like: surface size, herd size, economical characteristics and technical experience of Emater professionals too. Data was collected from dairy production's systems in Paraná state, northwest region, from 2006 to 2007 in the cities of Colorado, Itaguagé, Nossa Senhora das Graças and Santo Inácio. The interviews were semi-structured guided by a route. 26 variables were built starting from the transcription of the interviews, distributed in "management posts" like: feeding, surface management, herd and reproduction. It was defined from two to four classificatory levels inside each variable, but each level just happened once in each variable. Analysis was made using a multivariate statistical method called multiple correspondence analyses. In global analysis of all management posts, the first two factors " F1 and F2 " corresponded, respectively to 38.29% and 22.70% of the inertia, in other words, 60.99% of accumulation. The first factorial axis - F1, denotes variations among practices from low interference in the "days open", correlated to a less intensive forage paddock and in low scale; sanitary problems causing culling and cases which feeding demands are assisted; and culling per mastitis with more intensive parcels in the management and pasture control, in function of specie in the other side.. In other hand, F2 has opposition between, in first place: standard degree of interference in forage surface with sanitary culls and preventive observation SBC (Score of Body Condition), opposed to a low interference practices in "days open" and less controlled grass feeding related to surface. Finally the conclusion is: there are more than three groups defined by their strategies, denoted by F1 and F2, which the technique action must be appropriate for each one in the sense to identify their restriction points and the correct technical approach.